1995
DOI: 10.1111/j.1469-8986.1995.tb03303.x
|View full text |Cite
|
Sign up to set email alerts
|

Event‐related potentials to airway occlusion in young and old subjects

Abstract: Event-related potentials (ERPs) were recorded to both inspiratory and expiratory airway occlusion in young (21-28 years) and old (55-67 years) subjects under both attend and ignore conditions. Early and late components of the ERP (N1, P2, N2, P3) were observed to both types of occlusions in both conditions. Variations in these components were consistent in both direction and degree with those observed in oddball tasks employing exteroceptive stimuli. ERPs for breathing may serve to clarify sensory attributes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
47
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 35 publications
15
47
1
Order By: Relevance
“…Our results of the prolonged P3 latency and reduced P3 amplitude in the GAD group, compared to the healthy controls, are consistent with some notions given by the earlier RREP studies examining the effect of attention (Chan and Davenport, 2009;Harver et al, 1995;von Leupoldt et al, 2010bvon Leupoldt et al, , 2011aWebster and Colrain, 2000). In general, it has been suggested that P3 peak latency and amplitudes may be related to information processing speed and attentional resources allocation, respectively (Harver et al, 1995;Webster and Colrain, 2000).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results of the prolonged P3 latency and reduced P3 amplitude in the GAD group, compared to the healthy controls, are consistent with some notions given by the earlier RREP studies examining the effect of attention (Chan and Davenport, 2009;Harver et al, 1995;von Leupoldt et al, 2010bvon Leupoldt et al, , 2011aWebster and Colrain, 2000). In general, it has been suggested that P3 peak latency and amplitudes may be related to information processing speed and attentional resources allocation, respectively (Harver et al, 1995;Webster and Colrain, 2000).…”
Section: Discussionsupporting
confidence: 94%
“…In general, it has been suggested that P3 peak latency and amplitudes may be related to information processing speed and attentional resources allocation, respectively (Harver et al, 1995;Webster and Colrain, 2000). Specifically, Webster and Colrain (2000) found in their subject who presented a longer P3 latency during the counting RREP task also performed poorly in determining the duration of respiratory occlusions in the experiment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Controlled attention occurs when an added inspiratory load is applied to a subject actively attending to their breathing (load attend state). Significant differences between ignore and attend states have been reported for load-elicited brain activities, i.e., RREP N1 and P300 peak amplitudes were greater in the attend trials (Harver et al, 1995;Webster and Colrain, 2000). This suggests gating of automatic attention with load detection and gating-related modulation of controlled attention.…”
mentioning
confidence: 80%
“…We are aware of only one study which has tested age differences in respiratory-related evoked potentials (RREP, Harver et al, 1995). This study found reduced amplitude of RREPs in older compared to younger age and these age differences were more pronounced in later cognition-related components of RREPs.…”
Section: Central Pathways Between Age and Dyspneamentioning
confidence: 97%